2022
DOI: 10.1002/ece3.8656
|View full text |Cite
|
Sign up to set email alerts
|

Insect defoliation modulates influence of climate on the growth of tree species in the boreal mixed forests of eastern Canada

Abstract: Increasing air temperatures and changing precipitation patterns due to climate change can affect tree growth in boreal forests. Periodic insect outbreaks affect the growth trajectory of trees, making it difficult to quantify the climate signal in growth dynamics at scales longer than a year. We studied climate‐driven growth trends and the influence of spruce budworm (Choristoneura fumiferana Clem.) outbreaks on these trends by analyzing the basal area increment (BAI) of 2058 trees of Abies balsamea (L.) Mill.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 95 publications
0
1
0
Order By: Relevance
“…In addition, our study demonstrated that the SBW effect on growth is modulated significantly by climate (Figure 2.5 and Annex E). Climatic variation influences outbreak severity and the extent of defoliation (Gray, 2013), and, the degree of defoliation also determines the extent to which climate affects host tree growth (Boakye et al, 2022). Both the direct climate effect on growth and how climate mediates the effect of defoliation depend on the specific climate variable undergoing change (e.g., spring-summer temperature and precipitation) and time of the year.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study demonstrated that the SBW effect on growth is modulated significantly by climate (Figure 2.5 and Annex E). Climatic variation influences outbreak severity and the extent of defoliation (Gray, 2013), and, the degree of defoliation also determines the extent to which climate affects host tree growth (Boakye et al, 2022). Both the direct climate effect on growth and how climate mediates the effect of defoliation depend on the specific climate variable undergoing change (e.g., spring-summer temperature and precipitation) and time of the year.…”
Section: Discussionmentioning
confidence: 99%
“…BAI is already widely used in studies aiming to analyze the relationship between climate and tree growth [33,35,37,40,[55][56][57]. In fact, many studies have demonstrated that the use of BAI instead of RW generates higher correlations to tree biomass and wood volume gain [39,56,58].…”
Section: Bai Conversion As a Detrending Methods For Shrub Chronologiesmentioning
confidence: 99%
“…The conversion of ring width (RW) to ring area, or basal area increment (BAI), is a robust detrending approach that compensates for the ever-increasing perimeter of the cambium [33,34]. BAI has been used in studies aiming to characterize tree responses to environmental changes, and some of these studies confirm the effectiveness of converting RW into BAI as a detrending method [35][36][37][38]. Leblanc [39] demonstrated that RW measurements of pine and spruce species tend to cloud the relationship between a growth trend and its potential cause, and that BAI measurements are more closely related to the stem volume increment than RW data.…”
Section: Introductionmentioning
confidence: 99%